2018
DOI: 10.1097/pas.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CK7 Versus p16 as a Prognostic Biomarker in CIN 2

Abstract: Cervical intraepithelial neoplasia (CIN) 2 is an equivocal diagnosis, with p16 immunohistochemical positivity currently recommended for diagnostic confirmation. Biomarkers characteristic of squamocolumnar junction cells were recently found to be positive in almost all CIN 2 and CIN 3. CIN 1 lesions which express squamocolumnar junction markers (in particular cytokeratin 7 [CK7]) are associated with a higher rate of subsequent high-grade squamous intraepithelial lesion, suggesting that CK7 may be a useful progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
4
3
0
Order By: Relevance
“…Considering the previously cited studies, CDKN2A is a relevant biomarker to detect patients who unlikely to have progression of an intraepithelial lesion but will not indicate an unfavorable prognosis regardless of the previous histological diagnosis of CIN1 or CIN2. Umphress et al pointed out a high sensitivity for CDKN2A in predicting progression to CIN3 or worse (23) , similarly to our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Considering the previously cited studies, CDKN2A is a relevant biomarker to detect patients who unlikely to have progression of an intraepithelial lesion but will not indicate an unfavorable prognosis regardless of the previous histological diagnosis of CIN1 or CIN2. Umphress et al pointed out a high sensitivity for CDKN2A in predicting progression to CIN3 or worse (23) , similarly to our study.…”
Section: Discussionsupporting
confidence: 91%
“…A profile analysis of CDKN2A and CK7 markers showed that expression was positive for both in 64.7% of cases and was negative for 28.3%. It has also been found that positive expression of CDKN2A and CK7 increases the chance of progression from CIN2 to CIN3 or worse (23). In addition, this investigation indicated that CDKN2A specificity is greater than CK7, as observed in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…CK-7 is described as a marker for SCJ progenitor cells and is expressed in mostly in case of CIN II and CIN III. Higher the grade of CIN, higher the CK-7 expression (van der Marel et al, 2014;Umphress et al, 2018;Lima et al 2018). The site of origin of LSIL (CIN I) plays an important role in its progression.…”
Section: Discussionmentioning
confidence: 99%